2021
DOI: 10.3329/birdem.v12i1.57228
|View full text |Cite
|
Sign up to set email alerts
|

Precocious puberty: diagnosis and management

Abstract: Precocious puberty is commonly defined as puberty that starts before age 8 years in girls and 9 years in boys. The causes of it may range from a variant of normal development to various pathologic conditions. The etiology of precocious puberty is classified by the underlying pathogenesis into gonadotropin dependent central precocious puberty and peripheral precocious puberty which is independent of gonadotropin but due to different other causes. Variants of precocious puberty include premature thelarche, prema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(37 reference statements)
0
1
0
1
Order By: Relevance
“…In our study, 53.7% of cases with ICPP were overweight or obese. Studies have shown that precocious puberty is directly related to obesity and the age of onset of puberty was lower in girls who were overweight or obese [29][30][31]. Tasnima Ahmed et al, in a study on 71 patients with precocious puberty in Bangladesh, reported more cases in girls (71.8%).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 53.7% of cases with ICPP were overweight or obese. Studies have shown that precocious puberty is directly related to obesity and the age of onset of puberty was lower in girls who were overweight or obese [29][30][31]. Tasnima Ahmed et al, in a study on 71 patients with precocious puberty in Bangladesh, reported more cases in girls (71.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Однак важливо також враховувати, що ефективність цифрових технологій напряму залежить від контексту навчання та здатності студентів використовувати їх відповідно до своїх освітніх потреб. Це спостереження також визнано дійсним у дослідженні [3], в якому дослідники сформували набір заходів, які необхідно вжити для досягнення максимальної користі від навчання. Варто також погодитися з думкою висловленою у [4] про важливість педагогічної підтримки учнів в інтеграції цифрових технологій у STEM-освіту.…”
Section: деякі аспекти застосування цифрових технології у процесі вик...unclassified